Upcycling lignosulfonate into bio‐based polyhydroxybutyrate films for eco‐friendly antimicrobial and antioxidant food packaging - Teerin Chysirichote; Natthanon Phaiboonsilpa; Prueksuda Sakoolkaew (Journal of the Science of Food and Agriculture, 2025)
BACKGROUND: This study explored the upcycling of lignosulfonate, a by-product of the pulp and paper industry, into polyhydroxybutyrate (PHB)-based films for sustainable food packaging applications. Glycerol and lignosulfonate were incorporated to enhance film flexibility, antioxidant activity, and antibacterial properties, addressing the growing demand for functional and eco-friendly packaging materials. RESULTS: for yeast and mold count at 30 °C) and temperature coefficients (Q₁₀ = 2.16 and 1.78, respectively). This indicates strong thermal stability and effective control of microbial spoilage across 10-30 °C storage. CONCLUSION: Lignosulfonate-based PHB films demonstrate high potential as biodegradable and functional food packaging materials. Their ability to extend shelf life and maintain microbial stability supports the transition toward sustainable, clean-label, and low-emission packaging solutions. © 2025 Society of Chemical Industry.
Keywords: biodegradable polymer synthesis and properties; Advanced Cellulose Research Studies; Nanocomposite Films for Food Packaging